Inflammation and JNK's Role in Niacin-GPR109A Diminished Flushed Effect in Microglial and Neuronal Cells With Relevance to Schizophrenia - Ansarey, Sabrina H. (Frontiers in Psychiatry, 2021)
Schizophrenia is a neuropsychiatric illness with no single definitive aetiology, making its treatment difficult. Antipsychotics are not fully effective because they treat psychosis rather than the cognitive or negative symptoms. Antipsychotics fail to alleviate symptoms when patients enter the chronic stage of illness. Topical application of niacin showed diminished skin flush in the majority of patients with schizophrenia compared to the general population who showed flushing. The niacin skin flush test is useful for identifying patients with schizophrenia at their ultra-high-risk stage, and understanding this pathology may introduce an effective treatment. This review aims to understand the pathology behind the diminished skin flush response, while linking it back to neurons and microglia. First, it suggests that there are altered proteins in the GPR109A-COX-prostaglandin pathway, inflammatory imbalance, and kinase signalling pathway, c-Jun N-terminal kinase (JNK), which are associated with diminished flush. Second, genes from the GPR109A-COX-prostaglandin pathway were matched against the 128-loci genome wide association study (GWAS) for schizophrenia using GeneCards, suggesting that G-coupled receptor-109A (GPR109A) may have a genetic mutation, resulting in diminished flush. This review also suggests that there may be increased pro-inflammatory mediators in the GPR109A-COX-prostaglandin pathway, which contributes to the diminished flush pathology. Increased levels of pro-inflammatory markers may induce microglial-activated neuronal death. Lastly, this review explores the role of JNK on pro-inflammatory mediators, proteins in the GPR109A-COX-prostaglandin pathway, microglial activation, and neuronal death. Inhibiting JNK may reverse the changes observed in the diminished flush response, which might make it a good therapeutic target.